The Chinese Version of the Work Control Scale for Nurses: Modifying the Translation and Psychometric Testing - Fule Wen; Lin Wang; Zhiyin Fang; Jinjin Zhu; Yaqing Zhang (Elsevier, 2020)
Purpose: The aim of the study was to modify and test the psychometric properties of the Chinese version of the work control scale (C-WCS). Methods: The translated scale was administered to 840 nurses in Shanghai. Validity was assessed in terms of content validity and construct validity using exploratory factor analysis and confirmatory factor analysis. Internal consistency and test-retest reliability were estimated using Cronbach α and the intraclass correlation coefficient. Results: Psychometric analyses of the C-WCS indicate high reliability and good content and construct validity. Conclusion: The C-WCS has good psychometric properties and can be used as a valid tool for measuring work control among nurses in China. The C-WCS will help to further explore the correlations between perceived work control and organizational quality indicators such as nurses' satisfaction, job stress, well-being, or intention to stay. It can also be used in nursing outcome studies of work control strategies.